2013
DOI: 10.3389/fendo.2013.00008
|View full text |Cite
|
Sign up to set email alerts
|

Role of neuropeptide FF in central cardiovascular and neuroendocrine regulation

Abstract: Neuropeptide FF (NPFF) is an octapeptide belonging to the RFamide family of peptides that have been implicated in a wide variety of physiological functions in the brain including central cardiovascular and neuroendocrine regulation. The effects of these peptides are mediated via NPFF1 and NPFF2 receptors that are abundantly expressed in the rat and human brain. Herein, we review evidence for the role of NPFF in central regulation of blood pressure particularly within the brainstem and the hypothalamic paravent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 65 publications
1
36
0
Order By: Relevance
“…Moreover, Gcglobulin functions as a potent macrophage-activating factor, which greatly enhances phagocytic activity in macrophages (Yamamoto and Homma, 1991). Neuropeptide FF receptors 1 and 2 are membrane proteins activated by neuropeptides NPAF and NPFF, which belong to the RFamide family of peptides (Jhamandas and Goncharuk, 2013). It has been shown that NPFF neuropeptides reduce production of nitric oxide in macrophages and exhibit antiinflammatory activity in a mouse model (Sun et al, 2013).…”
Section: Candidate Genes Within the Targeted Regionmentioning
confidence: 99%
“…Moreover, Gcglobulin functions as a potent macrophage-activating factor, which greatly enhances phagocytic activity in macrophages (Yamamoto and Homma, 1991). Neuropeptide FF receptors 1 and 2 are membrane proteins activated by neuropeptides NPAF and NPFF, which belong to the RFamide family of peptides (Jhamandas and Goncharuk, 2013). It has been shown that NPFF neuropeptides reduce production of nitric oxide in macrophages and exhibit antiinflammatory activity in a mouse model (Sun et al, 2013).…”
Section: Candidate Genes Within the Targeted Regionmentioning
confidence: 99%
“…NPFF is known to be involved in morphine tolerance, adipogenesis, and anorectic activity (4045). In 2000, Tsutsui et al found a new RF-amide peptide, GnIH, in quail brain (5, 46).…”
Section: Evolutionary History Of Npff/npvf Qrfp and Prlhmentioning
confidence: 99%
“…14 Additionally, NPFF displays potent effects on regulation of the core temperature, 15 reduction in food intake and changes in arterial blood pressure. 16 The neuropeptide FF receptor family is part of the G protein-coupled receptor superfamily. Several groups cloned two genes encoding two different receptors (NPFFR1 and NPFFR2) and two precursors in several mammalian species.…”
mentioning
confidence: 99%